How Powerful CFOs Camouflage and Exploit Equity-Based Incentive Compensation - Collins, Denton (Journal of business ethics, 2018)
While numerous studies have examined the impact that powerful CEOs have on their compensation and overall firm decisions, relatively little is known about how powerful CFOs influence their compensation and important firm financial reporting and operational outcomes. This is somewhat surprising given the critical role CFOs play in the financial reporting process of a firm. Using managerial power theory (Bebchuk and Fried in J Econ Perspect 17:71–92, 2003) and the theory of power and self-focus (Pitesa and Thau in Acad Manag J 56(3):635–658, 2013), we predict that powerful CFOs employ a two-part strategy to camouflage excessive incentive compensation above what efficient contracting would dictate. First, powerful CFOs use their power and influence to negotiate shorter incentive pay duration to maximize the present value of their performance—based compensation. Second, when their incentive equity compensation vests, we suggest that CFOs manage earnings to further enhance their personal income. Consistent with our theoretical expectations, we find higher levels of income-increasing accrual-based earnings management and real transactions management, a potentially unethical practice, in firms with powerful CFOs who have short pay durations. We discuss the implications of our analysis in the context of mitigating CFO power and managing the ethical environment “tone at the top.”